Analisis Efisiensi Reksa Dana Syariah dengan Metode Data Envelopment Analisis (DEA) - Hamzah Robbani (LITERATUS, 2019)
According to Lawrence & Michael, "A portfolio is a collection of investment vehicles assembled to meet a common goal investment" means that the main purpose of the establishment of a portfolio is to obtain optimal results with minimal risk. This study analyzed the efficiency of mutual funds as well as to analyze the differences of each value efficiency sharia mutual fund shares. The results of this study indicate there is one mutual fund sharia efficient during years 2013-2015, namely mutual fund shares of CIMB - Principal Islamic Syariah Equity Growth. However, after variance analysis demonstrated no significant differences between the respective values of sharia equity fund. Then the hypothesis Ho is accepted with a value of 0,211 variants. Thus it can be concluded. The efficiency of mutual fund shares for 3 years not describe the significant value of different